Interactive Effects of CO2 Concentration and Water Regime on Stable Isotope Signatures, Nitrogen Assimilation and Growth in Sweet Pepper - Serret, María D.; Yousfi, Salima; Vicente, Rubén; Piñero, María C.; Otálora-Alcón, Ginés; del Amor, Francisco M.; Araus, José L. (Frontiers in Plant Science, 2018)
Sweet pepper is among the most widely cultivated horticultural crops in the Mediterranean basin, being frequently grown hydroponically under cover in combination with CO2 fertilization and water conditions ranging from optimal to suboptimal. The aim of this study is to develop a simple model, based on the analysis of plant stable isotopes in their natural abundance, gas exchange traits and N concentration, to assess sweet pepper growth. Plants were grown in a growth chamber for near 6 weeks. Two [CO2] (400 and 800 μmol mol−1), three water regimes (control and mild and moderate water stress) and four genotypes were assayed. For each combination of genotype, [CO2] and water regime five plants were evaluated. Water stress applied caused significant decreases in water potential, net assimilation, stomatal conductance, intercellular to atmospheric [CO2], and significant increases in water use efficiency, leaf chlorophyll content and carbon isotope composition, while the relative water content, the osmotic potential and the content of anthocyanins did change not under stress compared to control conditions support this statement. Nevertheless, water regime affects plant growth via nitrogen assimilation, which is associated with the transpiration stream, particularly at high [CO2], while the lower N concentration caused by rising [CO2] is not associated with stomatal closure. The stable isotope composition of carbon, oxygen, and nitrogen (δ13C, δ18O, and δ15N) in plant matter are affected not only by water regime but also by rising [CO2]. Thus, δ18O increased probably as response to decreases in transpiration, while the increase in δ15N may reflect not only a lower stomatal conductance but a higher nitrogen demand in leaves or shifts in nitrogen metabolism associated with decreases in photorespiration. The way that δ13C explains differences in plant growth across water regimes within a given [CO2], seems to be mediated through its direct relationship with N accumulation in leaves. The changes in the profile and amount of amino acids caused by water stress and high [CO2] support this conclusion. However, the results do not support the use of δ18O as an indicator of the effect of water regime on plant growth.